Case Report: Diagnosis of vertebral alveolar echinococcosis upon next-generation sequencing in a suspected tuberculosis - Song, Tiange; Peng, Shengkun; Zhou, Xiaoli; Jiang, Li; Zhang, Jie (Frontiers in Surgery, 2022)
Introduction: Alveolar echinococcosis (AE), caused by larval stages of Echinococcus multilocularis, is a rare zoonotic disease that mainly involves the liver. The diagnosis of extrahepatic AE is usually difficult. Here, we describe a rare case of vertebral alveolar echinococcosis with a suspected history of spinal tuberculosis, diagnosed by metagenomic next-generation sequencing (mNGS). Case Presentation: A 44-year-old woman presented with repetitive neck and back pain, with a surgical history of suspected spinal tuberculosis. Magnetic resonance imaging (MRI) showed cystic masses in the craniocervical junction region and effusion around lumbar vertebrae. Multiple culture tests were performed to detect tuberculosis and other pathogens through puncture of the effusion and of cerebrospinal fluid, but the results were all negative. Finally, mNGS of the effusion fluid was performed and Echinococcus multilocularis were detected. The results were further confirmed by Sanger sequencing. Conclusion: This case emphasizes a role of mNGS in the diagnosis of infectious diseases with unknown pathogen. As a newly emerged sensitive and accurate diagnostic strategy, mNGS provides clinicians an opportunity to clarify pathogens in complicated infectious cases, especially in patients with a history of multiple infections.